Persepsi Visual Fasad Bangunan di Kawasan Taman Ismail Marzuki Jakarta Sebagai Pembentuk Citra Kawasan - Annisa Tjahya Fitrianty; Herry Santosa; Jenny Ernawati (RUAS, 2024)
Challenges related to the visual aspects of the urban environment arise from the diverse interests, abilities, and perceptions of the community. These differences have an impact on the physical condition of the area, causing the visual process to be complicated and difficult to recognize. The revitalization of the Taman Ismail Marzuki area aims to revive the area as a center for arts and educational facilities. This effort includes the construction of a new building with various facilities. This study aims to examine the suitability of the visual elements of the façade of the building after revitalization, as well as its influence on the formation of the image of the area. This study uses a quantitative descriptive method. Data collection through surveys (questionnaires). The selection of respondent samples was carried out by accidental sampling, then analyzed using mean score analysis and multiple linear regression. The results show that the characteristics of the visual elements of the façade significantly affect the image of the area. Of the eight variables of the study, three main visual elements—architectural style, walls, and sun shading—highlight the characteristics of the area and play an important role in enhancing the image of Taman Ismail Marzuki.